Introduction to the Korea's cultural industry policy - Park Nark Jong (2023)
|When "Korean Wave '' began to gain popularity in the Asian region, mainly in the late '90s, the Korean government became interested in the cultural industry. The South Korean government focused on making institutional support in culture as the revision of existing cultural laws and regulations and the enactment of 10 new laws and regulations so that a good foundation of the cultural industry would be laid. Then, new organizations, funds related to the cultivation of new cultural industries were established with specific roles and responsibilities of the central and local governments in fostering the culturalindustry.